Temperature-dependent vortex motion in a square mesoscopic superconducting cylinder: Ginzburg-Landau calculations - Sardella, Edson [UNESP]; Malvezzi, André Luiz [UNESP]; Lisboa Filho, Paulo Noronha [UNESP]; Ortiz, Wilson Aires (American Physical Soc, 2006)
In this work we investigate the dynamics of vortices in a square mesoscopic superconductor. As time evolves we show how the vortices are nucleated into the sample to form a multivortex, single vortex, and giant vortex states. We illustrate how the vortices move around at the transition fields before they accommodate into an equilibrium configuration. We also calculate the magnetization and the free energy as functions of the applied magnetic field for several values of temperature. In addition, we evaluate the upper critical field.